Konsep Khiyar pada Jual Beli Pre Order Online Shop dalam Perspektif Hukum Islam - Dafiqah Hasanah; Mulyadi Kosim; Suyud Arif (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
This study aims to determine the practice of online pricing in the online store instagram Tiw's.id. the method used is descriptive qualitative with field research type. Khiyar right is the choise to cancel or establish a contract for both the seller and the buyer. The right of khiyar is a proof of the perfection of Islam in a business between two people who intend to create mutually acceptable transactions and avoid fraud. On a free purchase or purchase directly in general, you can check the items you want to buy like the disable items or the quality of the items, but its diffrent by buying online, the limited internet makes the khiyar right not noticed by both the seller and the buyer.